Ayahuasca and Its DMT- and β-carbolines – Containing Ingredients Block the Expression of Ethanol-Induced Conditioned Place Preference in Mice: Role of the Treatment Environment - Cata-Preta, Elisangela G.; Serra, Yasmim A.; Moreira-Junior, Eliseu da C.; Reis, Henrique S.; Kisaki, Natali D.; Libarino-Santos, Matheus; Silva, Raiany R. R.; Barros-Santos, Thaísa; Santos, Lucas C.; Barbosa, Paulo C. R.; Costa, José L.; Oliveira-Lima, Alexandre J.; et al. (Frontiers in Pharmacology, 2018)
Ayahuasca is a hallucinogenic beverage produced from the decoction of Banisteriopsis caapi (Bc) and Psychotria viridis (Pv), β-carboline- and N,N-dimethyltryptamine(DMT)-containing plants, respectively. Accumulating evidence suggests that ayahuasca may have therapeutic effects on ethanol abuse. It is not known, however, whether its effects are dependent on the presence of DMT or if non-DMT-containing components would have therapeutic effects. The aim of the present study was to investigate the rewarding properties of ayahuasca (30, 100 and 300 mg/kg, orally), Bc (132, 440 and 1320 mg/kg, orally) and Pv (3.75,12.5 and 37.5 mg/kg, i.p.) extracts and their effects on ethanol (1.8 g/kg, i.p.) reward using the conditioned place preference (CPP) paradigm in male mice. Animals were conditioned with ayahuasca, Bc or Pv extracts during 8 sessions. An intermediate, but not a high, dose of ayahuasca induced CPP in mice. Bc and Pv did not induce CPP. Subsequently, the effects of those extracts were tested on the development of ethanol-induced CPP. Ayahuasca, Bc or Pv were administered before ethanol injections during conditioning sessions. While Bc and Pv exerted no effects on ethanol-induced CPP, pretreatment with ayahuasca blocked the development of CPP to ethanol. Finally, the effects of a post-ethanol-conditioning treatment with ayahuasca, Bc or Pv on the expression of ethanol-induced CPP were tested. Animals were conditioned with ethanol, and subsequently treated with either ayahuasca, Bc or Pv in the CPP environment previously associated with saline or ethanol for 6 days. Animals were then reexposed to ethanol and ethanol-induced CPP was quantified on the following day. Treatment with all compounds in the ethanol-paired environment blocked the expression of ethanol-induced CPP. Administration of an intermediate, but not a high, dose of ayahuasca and Bc, as well as Pv administration, in the saline-paired compartment blocked the expression of ethanol-induced CPP. The present study sheds light into the components underlying the therapeutic effects of ayahuasca on ethanol abuse, indicating that ayahuasca and its plant components can decrease ethanol reward at doses that do not exert abuse liability. Importantly, the treatment environment seems to influence the therapeutic effects of ayahuasca and Bc, providing important insights into clinical practice.